A comparison of primidone, propranolol, and placebo in essential tremor, using quantitative analysis. Issue 1 (January 1986) - Gorman, W P; Cooper, R; Pocock, P; Campbell, M J
Abstract : The effects of placebo, propranolol and primidone were compared in 14 patients with essential tremor in a double blind, randomised, crossover study. Objective measures of tremor were obtained using an accelerometer with subsequent spectral analysis. Both propranolol (p less than 0.01) and primidone (p less than 0.01) gave significant improvement in tremor, but there was no significant difference in improvement between these drugs. Patients with higher dominant frequencies of tremor tended to respond to both drugs, while those with lower frequencies improved on one or other. There was no differential effect between the drugs with the frequency of tremor.